Domical ceiling of the mandapa of the Jain Temple - Temples of India Project Team (Jio Institute, 2024)
The square in plan mandapa (pillared hall) of the Jain Temple has a domical ceiling that is formed on concentric circles which diminish in size upto the centre. At the centre is suspending lotus medallion. The concentric rings that form the ceiling are plain. This type of ceiling is common in temples of Arthuna group of temples.